Teknologi keuangan, influencer media sosial, dan pengalaman keputusan investasi cryptocurrency: Peran literasi keuangan - Rijanto, Bonfilio Patrik; Utami, Novia (Universitas Kristen Maranatha, 2024)
This study evaluates the impact of financial technology usage, social media influencer presence, and investment experience on cryptocurrency investment decisions, considering financial literacy as a moderating factor. Financial technology refers to using technology in financial systems to create new service products, technologies, and business models. Social media influencers have gained fame and exert significant influence over their followers on social media platforms. Meanwhile, investment experience encompasses the duration of an investor's experience in trading transactions. Data for the study were obtained through a Google Form questionnaire distributed via social media to cryptocurrency investors aged 20 to 30 in the Jabodetabek area. Convenience sampling technique was employed to obtain a sample of 192 respondents. Data analysis was conducted using the SEM-PLS method with SmartPLS software. The results indicate that using financial technology and social media influencers positively influences cryptocurrency investment decisions, while investment experience does not significantly impact. However, financial literacy does not strengthen the influence of financial technology usage, social media influencers, and investment experience on cryptocurrency investment decisions. The research findings indicate that enhancing financial literacy among young investors should be prioritized. This can be achieved through formal education programs and financial literacy campaigns. Practitioners in the financial industry also need to provide financial education to their clients and offer educational content on cryptocurrency. These measures can help mitigate uncontrolled investment risks and promote informed investment decisions, thereby contributing to the stability of the financial market and the financial protection of the wider community.